Evolving Competitive Electricity Markets: an Enablement through Digital Approach - Ponraj, Jayaprakash; P R Ramakrishn, Dr.; ., . (International Journal of Engineering and Technology, 2018)
Introduction: Globally instituting competitive electricity markets focus on enablement of suppliers and end consumers digitally to benefit from open access. Open access transformation is a crucial entry point for the establishment of wholesale and retail competitive electricity markets. Technology reforms have been acknowledged worldwide in the electricity sector to orchestrate transforming electric industry business models. In addition to initiatives viz., unbundling (a kind of Industry stakeholder restructuring) of vertically integrated monopolies, upgrade of legal and deregulation frameworks, setting up of management guidelines for energy and wire charges, etc. guaranteeing right data availability and assuring the best informed decision making capabilities with a right validation and security of data to all stakeholders have been recognized as key enabler through an appropriate evidence-based survey recently conducted in the state of Tamilnadu across consumers and suppliers of electricity. This paper is focussed on various approaches for digitally transforming transmission and distribution stakeholders of the electricity industry with an objective to advance reliability, accomplish costs and sales economically, sustain the availability, assure the security and energy sustainability for providing safe electricity supply and thus to empower superior benefits to the consumers.Research Methodology: The study examined prospects and challenges for the establishment of wholesale and retail competitive electricity market in Tamil Nadu, India. This study included the survey of a sample size of 325 individuals from electricity consumersâ€™, and 80 individuals from suppliersâ€™ is collected in Tamil Nadu using a structured questionnaire.Findings: The study proposes appropriate digital technology strategy along with high spot on proposed governance, legal and regulatory framework. This study deliberates various plans of Orchestrations and an approach to challenge the prospective Obstacles towards the establishment of competitive electricity markets in Tamil Nadu state.Implications of the study: The study discusses influences on stakeholders of the electricity market in Tamil Nadu state to consider developing technology strategies.JEL Classification: J11, C02, C15, C53, C55, C61, F17, F63, F64Â